Prediksi Kebangkrutan: Dapatkah Kecakapan Manajerial Mampu Mengantisipasi Dampak Pandemi Covid-19? - Veronica Rasmi Febrianty Siahaan; Ari Budi Kristanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The COVID-19 pandemic has an impact on society, companies and countries. This causes a decrease in the market’s purchasing power, and brings risk to the businesses’ sustainability. The purposes of this research are to examine whether the impact COVID-19 pandemic had a positive effect on prediction bankruptcy and to examine the effect of historical managerial ability in anticipating pandemic impact toward bankruptcy prediction. This is a quantitative research which uses secondary data, namely financial information and content of information disclosure report of manufacturing companies. The research sample are 67 manufacturing companies. Sample based on purposive sampling with criterias that manufacturing companies are listed on Indonesia Exchange Stock and have complete data on research variables. The measurement of the impact COVID-19 pandemic uses composite score, then bankruptcy prediction uses Altman Z-Score, and managerial ability score uses DEA. This research uses binary logistic regression and moderated regression analyze to test the hypothesis. The research proves that more serious impact COVID-19 pandemic on company is the more predictable the company will go bankrupt. Other results show that historical managerial ability cannot weaken impact COVID-19 pandemic on prediction bankruptcy. Keywords: impact COVID-19 pandemic, bankruptcy prediction, managerial ability